Best Practices in the Development, Translation, and Cultural Adaptation of Patient-Reported Outcome Measures for Adults With Hearing Impairment: Lessons From the Cochlear Implant Quality of Life Instruments - Laplante-Lévesque, Ariane; Dubno, Judy R.; Mosnier, Isabelle; Ferrary, Evelyne; McRackan, Theodore R. (Frontiers in Neuroscience, 2021)
This manuscript summarises available evidence-based best practices in the development, translation, and cultural adaptation of one type of outcome measure for adults with hearing impairment, patient-reported outcome measures (PROMs). It presents the development of the Cochlear Implant Quality of Life (CIQOL) instruments and the ongoing translation and cultural adaptation of the CIQOL-35 Profile from English to French as case studies and discusses useful lessons for selecting, developing, translating, culturally adapting, and using PROMs. Relevant best practice guides are introduced, described and their steps are illustrated with examples. Future trends in hearing-related PROMs, including computerised adaptive testing, patient-reported experience measures (PREMs), economic evaluation and allocation of scarce resources, and PROMs in low-resource settings, are discussed. The manuscript concludes on the lessons that can be learned from implementation science for the successful and sustainable integration of PROMs in clinical practice.